ثلاثية الراء في ديوان الخنساء: الدهر، القدر، القبر - شهوان، وفاء سعيد (جامعة قاصدي مرباح - ورقلة, 2018)
تناولت الدراسة ثلاثة محاور (الدهر والقدر والقبر) وبحثت في دلالاتها عند الخنساء في الجاهلية وبعد الإسلام. وسميت البحث ثلاثية الراء في ديوان الخنساء، واعتمدت في الدراسة على المنهج النفسي، فطرحت المفهوم وناقشته بالسؤال والجواب ودعمته بالشواهد الشعرية التي تثبت دلالة المحور، كما وظّفت التناص في ثناياها وتوصلت الدراسة إلى نتائج أبرزها: أن الدهر ألهم الخنساء الحكمة وأن إيمانها بالقضاء والقدر جعلها صحابية جليلة، وأن القبر رسخ إيمانها وهذب نفسها ونظم أفكارها. وأتبعته بخاتمة سجلت فيها نتائج البحث العامة والخاصة.
The study dealt with Tri "R" cycles, i.e. (age, fate and grave). The researcher studied the meanings of these themes during Al- Khansa'a's life dark age i.e. (Aljaahiliyyah), and hers after embracing Islam. The researcher relied on the psychological application in presenting the above said concepts and presenting them through the question and answer methodology, which supported by the poetic evidences that prove the significance of the study, which helped the researcher to come out with a number of general and specific results related to the research themes . As far as the contextalization is concerned, the researcher concluded that the wisdom of Al-khansa'a was inspired by the concept of era, whereas her belief in Fatalism has made her a great companion, however, Al-khansa'a's ideas, its shape and setting were infleunced by her certainty on the grave .
Keywords: الشعر العربي -- شعر الرثاء -- ديوان الخنساء -- صخر -- الدهر -- القدر -- القبر